VALUE ORIENTATIONS OF MODERN STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with some problems of value orientations in students' life. The analysis of value orientations in students’ life in higher educational establishments of economy and pedagogy is provided.
Keywords: 1